The Grey Matters: The Use and Abuse of East/West Taxonomies. (11th May 2015) - Haynes, Sarah
Abstract : In my 2013 Bulletin blog post on the categorization of religious traditions as eastern or western I focused on my work as an academic studying Tibetan Buddhism in North America and my experiences teaching eastern religions to students at a post-secondary institution in the United States. Expanding on my earlier contribution, here I focus my attention on the challenges and responses related to the east/west taxonomies in the context of my research and teaching.